Practical Implementation of Hydrogen in Buildings: An Integration Model Based on Flowcharts and a Variable Matrix for Decision-Making - Sara Dorregaray-Oyaregui; César Martín-Gómez; Amaia Zuazua-Ros; Mónica Aguado (Energies)
Buildings are major energy consumers, accounting for a significant portion of global energy consumption. Integrating hydrogen systems, electrolyzers, accumulation, and fuel cells is proposed as a clean and efficient energy alternative to mitigate this impact and move toward a more sustainable future. This paper presents a systematic procedure for incorporating these technologies into buildings, considering building engineers, and stakeholders. First, an in-depth analysis of buildings’ main energy consumption parameters is conducted, identifying areas of energy need with the most significant optimization potential. Next, a detailed review of the various opportunities for hydrogen applications in buildings is conducted, evaluating their advantages and limitations. Performing a scientific review to find and understand the requirements of building engineers and the stakeholders has given notions of integration that emphasize the needs. As a result of the review process and identifying the needs to integrate hydrogen into buildings, a flowchart is proposed to facilitate decision-making regarding integrating hydrogen systems into buildings. This flowchart is accompanied by a matrix of variables that considers the defined requirements, allowing for combining the most suitable solution for each case. The results of this research contribute to advancing the adoption of hydrogen technologies in buildings, thus promoting the transition to a more sustainable and resilient energy model.